Evaluasi Pembelajaran Hifdlul Qur’an dalam Rangka Peningkatan Target Hafalan di Pondok Pesantren Bahrul Ulum Simo Boyolali - Abdullah, A; Subando, Joko (MAMBA'UL 'ULUM, 2026)
This study aims to describe the evaluation of hifdlul Qur’an learning in improving students’ memorization targets at Pondok Pesantren Bahrul Ulum Simo Boyolali. This research employed a descriptive qualitative approach with field research design. The data sources consisted of the kiai or pesantren leader, program manager, Qur’an teachers, dormitory supervisors, and students participating in the memorization program. Data were collected through observation, interviews, Google Forms, and documentation. The findings indicate that hifdlul Qur’an learning is implemented through tahsin, ziyādah, memorization submission, murāja‘ah, and periodic evaluation. The evaluation system includes assessment of memorization fluency, tajwid accuracy, pronunciation of letters, consistency of murāja‘ah, and documentation of students’ memorization progress. The achievement of memorization targets is influenced by students’ abilities, motivation, discipline, teacher guidance, supervisor monitoring, and the pesantren environment. Supporting factors include the leader’s support, halaqah system, intensive guidance, and Qur’anic learning culture. Inhibiting factors include differences in students’ abilities, weak murāja‘ah discipline, dense pesantren activities, and less optimal progress recording. This study confirms that systematic, continuous, and student-centered evaluation can improve memorization targets with better quality.